Inability to access health and social services associated with mental health among people who inject drugs in a Canadian setting. (1st November 2016) - Wang, Linwei; Panagiotoglou, Dimitra; Min, Jeong Eun; DeBeck, Kora; Milloy, M.J.; Kerr, Thomas; Hayashi, Kanna; Nosyk, Bohdan
Highlights: Over 65% of people who inject drugs (PWID) reported inability to access care in Vancouver (2005–2015). Mental health conditions were associated with increased barriers to access care. Need to assist PWID with mental health conditions to navigate the healthcare system. Need to seek and treat mental health conditions in settings that serve PWID. Abstract: Background: People who inject drugs (PWID) face barriers to healthcare due to reasons including comorbidity. We evaluated access to health and social services by three of the most prevalent comorbid conditions among PWID: HIV, hepatitis C (HCV), and mental health, in an urban setting in Canada. Methods: Data were derived from prospective cohorts of community-recruited PWID between 2005 and 2015. HIV and HCV serostatuses were based on antibody tests, while mental health conditions and inability to access health and social services (barriers to access) were determined by participants' self-report. We employed generalized linear mixed models controlling for confounders to examine associations between health conditions and barriers to access. Results: Among 2494 participants, 1632 (65.4%) reported barriers to access at least once over a median of seven (IQR: 3, 12) semi-annual assessments. Mental health conditions were independently associated with increased odds of reporting barriers (adjusted Odds Ratio (aOR): 1.45, 95% Confidence Interval (CI): 1.32, 1.58), while HIV was not (aOR: 0.96, 95% CI: 0.85, 1.08), and HCV was associated with decreased odds (aOR: 0.80, 95% CI: 0.69, 0.93). The associations between mental health conditions and barriers to access were consistent among PWID without HIV/HCV (aOR: 1.35, 95% CI: 1.10, 1.65), with HCV mono-infection (aOR: 1.55, 95% CI: 1.37, 1.75), and HCV/HIV co-infection (aOR: 1.36, 95% CI: 1.15, 1.60). Conclusions: Targeted strategies to seek and treat mental health conditions in settings that serve PWID, and assist PWID with mental health conditions in navigating healthcare system may improve the publicly-funded health and social services.